Long-term stable efficacy of botulinum toxin A in facial movement disorders with no need for increasing dose. Issue 25 (25th June 2021) - Badarny, Samih; Ibrahim, Raphiq; Susel, Zvi; Zaina, Adnan; Nasar, Rema; Badarny, Yazid
Abstract : Abstract: Botulinum toxin A is considered an effective treatment for involuntary facial movements. We examined whether treatment efficacy maintained or changed over time with two products, Botox and Dysport, in patients with hemifacial spasm, facial synkinesis and benign essential blepharospasm. We retrospectively investigated 87 consecutive patients (51 women, 36 men) who had undergone treatment for ≥6 years. Long-term effects, as well as side effects of Botox or Dysport local injections were evaluated. The first three treatments were considered the titration period and not taken into account when testing for dose changes. Mean treatment duration was 10 years (range 6–11, SD 1.0), 2441 treatments were administered, 1162 with Botox and 1279 with Dysport, the two brands were interchanged as needed. Good to full improvement was seen in 90% of patients both with both brands. Injection doses and treatment responses were consistent during the study with both drugs. No major side effects were reported, and relatively few minor adverse events were reported, with clear reduction from the titration period (6.1%), to the remainder of the study (3.9%). Botulinum toxin (BTX-A) is a satisfactory long-term treatment without need for dose increase over. Both Botox and Dysport were effective when used interchangeably.